Fast Fulfillment : The Machine That Changed Retailing. - Das, Sanchoy. (Studien Zum Physik- und Chemielernen Series, 2021)
Managers are frustrated just reading about how great Amazon is, and how startups are innovating fantastic technology driven processes. Here is the book, written in a simple easy to read style which unravels the technical mystery of the fulfillment machine. It levels the knowledge field, reveals the secrets of fast fulfillment, and helps the reader construct a plan to innovate and be ready to face the disruptors. This book provides insights and process details of how to design and build disruptive innovations, so that you are not flying blind or just throwing darts in an effort to pivot/expand to the online order fulfillment world.